Saliva as a potential tool for diagnosis of dry mouth including Sjögren's syndrome. (15th May 2014) - Ohyama, K; Moriyama, M; Hayashida, J‐N; Tanaka, A; Maehara, T; Ieda, S; Furukawa, S; Ohta, M; Imabayashi, Y; Nakamura, S
<x xml:space="preserve">Abstract</x> Objectives Recently, the use of saliva as a diagnostic tool has gained considerable attention because it is non‐invasive and easy to perform repeatedly. In this study, we focused on soluble molecules in saliva to establish a new diagnostic method for xerostomia. Materials and Methods Saliva was obtained from 90 patients with Sjögren's syndrome (SS), 22 patients with xerostomia associated with neurogenic/neuropsychiatric disorders and drugs (XND), 30 patients with radiation‐induced xerostomia (RX), and 36 healthy controls. Concentrations of helper T (Th) cytokines in saliva were measured by flow cytometric analysis. Concentrations of secretory IgA (SIgA) and chromogranin A (CgA) were measured by ELISA. Results Unstimulated and stimulated whole saliva from patients with SS, XND, and RX was significantly reduced compared with controls. Th1 and Th2 cytokines from SS patients were significantly higher than controls. Furthermore, Th2 cytokines were closely associated with strong lymphocytic accumulation in salivary glands from SS patients, while Th1 and Th17 cytokines were negatively associated. SIgA levels were not significantly different between all patient groups and controls. CgA levels from XND patients were significantly higher than controls. Conclusions The measurement of cytokines, CgA, and SIgA in saliva is suggested to be useful for the diagnosis of xerostomia and also to reveal disease status.